Pengaruh Pemberian Ekstrak Akar Alang-Alang terhadap Hati Mencit yang Menderita Gangguan Patologi (THE INFLUENCE OF THE ROOT OF SEDGE GRASS EXTRACTION ON LIVER OF MICES THAT TO SUFFER A PATHOLOGICAL DAMAGED) - Berata, I Ketut; Winaya, Ida Bagus Oka (Jurnal Veteriner; Vol 4 No 1 (2003), 2016)
Abstak dapat dibaca pada Full Text Abstract can be read at Full Text
Keywords: extract of the sedge grass root, liver damage, mice, repair